A debreceni emlékezet lokális és nem lokális rétegei - Imre, László (Studia Litteraria, 2021)
One of the “hidden” merits of the volume titled A debreceniség mintázatai: Városi identitás és a lokális emlékezet rétegei a kora újkortól napjainkig (Patterns of Debrecenness: Layers of Urban Identity and Local Memory from Early Modern Era to the Present) is that the authors approach the extraordinarily rich history and present of Debrecen with impeccable evaluation and local patriotism enriched with well-aimed, strict criticism. It should be emphasised that some of the authors “works ahead” for the posterity, when, for instance, discussing the architecture in Debrecen in the past few decades they provide foundation for future centuries on how to interpret the past. It is also worth mentioning that the emotionally loyal caretakers of Debrecen’s past, in almost all the cases, have a somewhat ambivalent relationship with the topic, besides identification they also maintain a certain critical distance.